Systematic review of the impact of non-alcoholic fatty liver disease on mortality and adverse clinical outcomes for individuals with chronic kidney disease. Issue 9 (28th September 2020) - Hydes, Theresa; Buchanan, Ryan; Kennedy, Oliver J; Fraser, Simon; Parkes, Julie; Roderick, Paul
Abstract : Objectives: To investigate if non-alcoholic fatty liver disease (NAFLD) impacts mortality and adverse outcomes for individuals with chronic kidney disease (CKD). Design: Systematic review. Data sources: PubMed, EMBASE and Web of Science were searched up to 1 February 2020 with no restriction on the earliest date. Eligibility criteria for selecting studies: Observational cohort studies that reported either the risk of all-cause mortality, incidence of non-fatal cardiovascular events (CVE) or progression of kidney disease among adults with established CKD who have NAFLD compared with those without. Data extraction and synthesis: Two reviewers extracted data and assessed bias independently. Results: Of 2604 records identified, 3 studies were included (UK (n=852), South Korea (n=1525) and USA (n=1413)). All were judged to have a low or moderate risk of bias. Data were insufficient for meta-analysis. Two studies examined the influence of NAFLD on all-cause mortality. One reported a significant positive association for NAFLD with all-cause mortality for individuals with CKD (p<0.05) (cardiovascular-related mortality p=ns), which was lost following adjustment for metabolic risk factors; the second reported no effect in adjusted and unadjusted models. The latter was the only study to report outcomes for non-fatal CVEs and observed NAFLD to be an independent risk factor for this (propensity-matched HR=2.00, p=0.02). Two studies examined CKD progression; in one adjusted rate of percentage decline in estimated glomerular filtration rate per year was found to be increased in those with NAFLD (p=0.002), whereas the other found no significant difference. Conclusions: Few studies have examined the influence of NAFLD on prognosis and major adverse clinical outcomes within the CKD population. The studies identified were diverse in design and results were conflicting. This should be a focus for future research as both conditions continue to rise in prevalence and have end-stage events associated with significant health and economic costs. PROSPERO registration number: CRD42020166508.